The use and abuse of language by a Chicano from Aztlán (both words unknown) - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
When the rich steal from the poor it is called business, when the poor protest it is called violence. When the natives follow their millennial migrations across America, they are called undocumented illegal aliens. When the Europeans, invade, commit genocide and steal America, they call themselves immigrants and pilgrims. The united Nations and the Red Cross are concerned and sometimes respond to atrocities throughout the world, never to atrocities in the United States of America and its borderland wall of death more than 1000 miles long, so long the boundaries can be seen from outer space!